Squamous papilloma in the floor of the mouth: A rare presentation - Nair, Priya K; Varma, Beena; Ramachandran, Anu; Savithri, Vindhya; Kumar, Krishna S; Shanmughan, Aravind M (Indian Journal of Case Reports, 2021)
Oral squamous papilloma is a benign epithelial tumor that constitutes around 2.5% of all oral verruco-papillary lesions and is caused by the Human Papilloma Virus (HPV). HPV subtypes 6 and 11, which are considered to be of low carcinogenic potential are usually associated with oral squamous papilloma. Though there is no site predilection as such, the most common intraoral sites reported are tongue, lips, buccal mucosa, gingiva, and palate. This is a case report describing the case of a 69-year-old male patient who reported the complaint of growth on the floor of the mouth for four years which was diagnosed as squamous papilloma on the floor of the mouth which is a relatively uncommon site.